Pixel type CZT detector and passivation process thereof
By using hydrogen peroxide solution on the CZT detector to generate an oxide layer, combined with photolithography and etching liquid treatment, the existing passivation methods are solved, and efficient and safe passivation effect is achieved. Reduces leakage current and improves detector performance.
Patent Information
- Application Number
- CN202411154092.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-20
AI Technical Summary
The passivation methods of existing CZT detectors are inefficient and harmful. Traditional methods such as NH4F are highly toxic, NaClO passivation time is long and requires multiple solutions to remove heteroatoms. The preparation efficiency of existing high resistance passivation layer structures is low.
The hydrogen peroxide solution is used to form an oxide layer, and a photoresist-oxide layer structure is formed by photolithography and etching liquid treatment. The electrode is plated to ensure that the oxide layer is connected to the electrode. The entire process is short-lived and high-efficiency and no harmful substances are generated.
A safe and efficient passivation process is achieved, which reduces leakage current, improves detector performance, and avoids the generation of harmful substances.
Smart Images

Figure CN119170693A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of CZT crystal passivation, in particular to a pixel-type CZT detector and a passivation process thereof. Background Art
[0002] In the preparation of pixel detectors, regarding the pixel gap passivation, effective passivation can greatly reduce the detector leakage current and improve the performance of the detector. The traditional passivation methods include NH 4 F passivation and NaClO passivation, while NH 4 F is toxic and will greatly endanger the health of operators during the passivation process. In addition, the process is complicated and inefficient. The passivation time of NaClO is relatively long. After passivation, it is necessary to use a variety of solutions to remove other heteroatoms introduced into the crystal.
[0003] In the prior art, an invention patent (CN112216749A) discloses a cadmium zinc telluride (CZT) crystal detector with a high-resistance passivation layer and a preparation method thereof. The structure of the CZT single crystal is a sandwich structure of a high-resistance passivation layer-a semiconductor-a high-resistance passivation layer. In the preparation, high-purity Cd, Zn, and Te materials with a purity of 99.99999% are selected as raw materials for growing CZT crystals by a vertical Bridgman method. After the crystals are obtained, they are sliced and diced to obtain the required substrate. After polishing and etching, a high-resistance passivation layer is grown on the sample by a radio frequency magnetron sputtering deposition method. After photolithography and plasma etching, an Au electrode is further deposited on the single crystal by an electron beam evaporation method. This preparation method has low efficiency.
[0004] Based on this, the technical problem to be solved in this case is: to provide a pixel-type CZT detector and its passivation process. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a pixel-type CZT detector passivation process. In this process, the CZT crystal is immersed in a hydrogen peroxide solution to generate an oxide layer on the surface of the CZT crystal, and a photoresist is formed by photolithography. The oxide layer outside the photoresist area is then etched away by an etching solution, and finally an electrode is plated. In this way, the oxide layer can be connected to the electrode of the plated electrode to complete the passivation. The entire passivation process takes a short time and is highly efficient. At the same time, the present invention also provides a pixel-type CZT detector obtained based on this process.
[0006] The technical solution of the present invention is:
[0007] A pixel type CZT detector passivation process comprises the following steps:
[0008] Step 1: Soaking the CZT crystal in a hydrogen peroxide solution having a mass fraction of 30 to 65% of hydrogen peroxide for 1 to 10 minutes to obtain a CZT crystal having an oxide layer;
[0009] Step 2: Photolithography the CZT crystal processed in step 1, covering the photolithography area with a layer of photoresist, and then immersing the CZT crystal containing the photoresist in an etching solution to etch the oxide layer outside the photoresist;
[0010] Step 3: The CZT crystal processed in step 2 is cleaned, electrode-plated, and photoresist stripped in sequence to obtain a CZT crystal with an electrode connected to an oxide layer.
[0011] In the actual application process, the staff placed the CZT crystal in a hydrogen peroxide solution with a mass fraction of 30-65% hydrogen peroxide, and immersed it in the hydrogen peroxide solution to form an oxide layer on the surface of the CZT crystal. The specific chemical equation is:
[0012] ①CdZnTe+H 2 O 2 =Cd(OH) 2 +Zn(OH) 2 +Te;
[0013] ②Te+2H 2 O 2 =H 2 TeO 3 +H 2 O;H 2 TeO 3 +H 2 O 2 +H 2 O=Te(OH) 6 ;
[0014] ③H 2 TeO 3 =TeO 2 +H2O.
[0015] According to the above chemical equations ① to ③, it can be known that an oxide layer mainly composed of tellurium oxide is finally formed. Specifically, the thickness of the required oxide layer is 100 to 200 nm. The CZT crystal with the oxide layer is photolithographically processed so that the CZT crystal is covered with a layer of photoresist in the photolithographic area on the surface of the oxide layer. Finally, it is immersed in an etching solution to etch away the oxide layer of the CZT crystal not covered by the photoresist to obtain a photoresist-oxide layer-CZT crystal structure. It is then washed with water, plated with electrodes, and then the photoresist is stripped off to obtain a CZT crystal with electrodes connected to the oxide layer, completing passivation. Through this passivation method, no harmful substances are generated during the passivation process, and the entire passivation process takes a short time, which means it is safe and efficient.
[0016] Preferably, the etching solution in step 2 is a bromoethylene glycol solution, the mass fraction of bromoethylene glycol in the bromoethylene glycol solution is 1-4%, more preferably, the mass fraction of bromoethylene glycol in the bromoethylene glycol solution can be selected as 1%, 2%, 3%, 4%, preferably, the immersion time is 4-28s, more preferably, the immersion time can be selected as 4s, 10s, 16s, 22s, 28s.
[0017] Furthermore, the etching solution is specifically a bromoethylene glycol solution, and the mass fraction of bromoethylene glycol in the bromoethylene glycol solution is 1 to 4%, and the immersion time is 4 to 28 seconds. Specifically, when the mass fraction of bromoethylene glycol in the bromoethylene glycol solution increases, the probability of the photoresist being dissolved increases; when the mass fraction of bromoethylene glycol in the bromoethylene glycol solution decreases, the time for etching the oxide layer will increase and the efficiency will decrease.
[0018] Preferably, the mass fraction of bromoethylene glycol in the bromoethylene glycol solution is 2%, and the immersion time is 10 seconds.
[0019] Furthermore, under the premise of ensuring etching efficiency and not dissolving the photoresist, the mass fraction of bromoethylene glycol in the bromoethylene glycol solution is 2%, and the immersion time is 10S, which is the best.
[0020] Preferably, the mass fraction of hydrogen peroxide in the hydrogen peroxide solution in step 1 is 50%, and the immersion time is 4 minutes.
[0021] In the process of generating the oxide layer, it can be seen from the chemical equation ① that CZT crystal immersed in hydrogen peroxide solution will generate Cd(OH) 2 and Zn(OH) 2 When the concentration of hydrogen peroxide increases, the rate of oxide layer formation increases, which can easily lead to the oxide layer converting Cd(OH) into 2 and Zn(OH) 2 Locked between the oxide layer and the CZT substrate, this will affect the subsequent etching effect. During the etching process, when Cd(OH)2 and Zn(OH) 2 After the upper oxide layer is etched away, it is easy to etch the CZT substrate, resulting in an uneven surface of the etched substrate. When the concentration of the hydrogen peroxide solution is reduced, the efficiency is reduced.
[0022] Furthermore, the photolithography in step 2 is negative photolithography, and the photoresist formed by the negative photolithography is located above the oxide layer.
[0023] Preferably, the photolithography method used is negative photolithography, which makes it easier for workers to visually observe the area that needs to be covered by the photoresist. Positive photolithography can also implement this solution, but it is not easy to observe visually compared to negative photolithography. Specifically, whether it is negative photolithography or positive photolithography, a layer of photoresist is covered on the oxide layer.
[0024] More preferably, the step 3 is specifically: washing away the bromoethylene glycol solution remaining on the CZT crystal with water, plating an electrode on the CZT crystal, and finally stripping off the photoresist to obtain a CZT crystal with the electrode connected to the oxide layer.
[0025] During the specific operation, the bromoethylene glycol solution remaining on the CZT crystal is washed away with water to prevent the bromoethylene glycol solution from continuing to etch the CZT substrate. After washing, a gold electrode is plated on the CZT crystal. Finally, the photoresist is stripped off to obtain a CZT crystal with a gold electrode connected to an oxide layer. The oxide layer can provide passivation, thereby reducing leakage current.
[0026] More preferably, the photoresist stripping is performed by immersing the CZT crystal after electrode plating in a stripping solution until the photoresist falls off and then taking it out to obtain a CZT crystal with an electrode and an oxide layer connected.
[0027] Furthermore, the photoresist is stripped by immersing the CZT crystal with the photoresist in a stripping solution, waiting for the photoresist to fall off and then taking out the CZT crystal. In this way, stripping the photoresist is more convenient and quick.
[0028] Preferably, the step 1 is specifically as follows: before the CZT crystal is immersed in the hydrogen peroxide solution, the CZT crystal is immersed in a bromomethanol solution, wherein the mass fraction of bromomethanol in the bromomethanol solution is 1-5%, and the immersion time is 30-300s, and the CZT crystal is immersed in the hydrogen peroxide solution immediately after being immersed in the bromomethanol solution.
[0029] Furthermore, before immersing the CZT crystal in the hydrogen peroxide solution, the mechanical damage on the surface of the CZT crystal will be removed first. In this embodiment, the mechanical damage is removed by immersing the CZT crystal in a bromomethanol solution. In particular, the mass fraction of bromomethanol in the bromomethanol solution is selected to be 1-5%, and the immersion time is 30-300S. Specifically, after immersion, in order to avoid contamination or oxidation of the CZT crystal, it is necessary to immediately immerse the CZT crystal in a hydrogen peroxide solution. When the CZT crystal is oxidized before being immersed in the hydrogen peroxide solution, the surface of the CZT crystal cannot fully generate an oxide layer, and the thickness of the CZT oxide layer is different, which affects the surface uniformity of the CZT crystal and the density of the oxide layer.
[0030] In addition, the present application also discloses a pixel-type CZT detector, which is manufactured according to the above-mentioned pixel-type CZT detector passivation process.
[0031] One of the above technical solutions of the present invention has at least one of the following advantages or beneficial effects:
[0032] The present invention immerses the CZT crystal in a hydrogen peroxide solution so that an oxide layer is generated on the surface of the CZT crystal, and a photoresist is formed by photolithography, and then the oxide layer outside the photoresist area is etched away by an etching solution, and finally an electrode is plated. In this way, the oxide layer can be connected to the electrode of the plated electrode to complete the passivation. The entire passivation process takes a short time and is highly efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] See also Figure 1 ;
[0037] Step 1: Soak the CZT crystal in a 30wt% hydrogen peroxide solution for 10 minutes to obtain a CZT crystal with an oxide layer;
[0038] Step 2: Photolithography the CZT crystal processed in step 1, covering the photolithography area with a layer of photoresist, and then immersing the CZT crystal containing the photoresist in a 2wt% bromoethylene glycol solution to etch the oxide layer outside the photoresist, and the etching time is 10s;
[0039] Step 3: The CZT crystal processed in step 2 is cleaned, electrode-plated, and photoresist stripped in sequence to obtain a CZT crystal with an electrode connected to an oxide layer.
[0040] Example 2
[0041] The difference between Example 2 and Example 1 is that the concentration of the hydrogen peroxide solution used is 50 wt % and the immersion time is 2 min.
[0042] Example 3
[0043] The difference between Example 3 and Example 2 is that the concentration of the hydrogen peroxide solution used is 65 wt %.
[0044] Example 4
[0045] The difference between Example 4 and Example 2 is that the concentration of the bromoethylene glycol solution used is 1 wt % and the immersion time is 28 s.
[0046] Example 5
[0047] The difference between Example 5 and Example 2 is that the concentration of the bromoethylene glycol solution used is 4 wt % and the immersion time is 4 s.
[0048] Example 6
[0049] The difference between Example 6 and Example 2 is that the etching solution used is a 2 wt % bromine methanol solution and the immersion time is 40 s.
[0050] Example 7
[0051] The difference between Example 7 and Example 2 is that the concentration of the bromoethylene glycol solution used is 10 wt % and the immersion time is 4 s.
[0052] Comparative Example 1
[0053] Step 1: Soak the CZT crystal in a 70wt% hydrogen peroxide solution for 2 minutes to obtain a CZT crystal with an oxide layer;
[0054] Step 2: Photolithography the CZT crystal processed in step 1, covering the photolithography area with a layer of photoresist, and then immersing the CZT crystal containing the photoresist in a 2wt% bromoethylene glycol solution to etch the oxide layer outside the photoresist, and the etching time is 10s;
[0055] Step 3: The CZT crystal processed in step 2 is cleaned, electrode-plated, and photoresist stripped in sequence to obtain a CZT crystal with an electrode connected to an oxide layer.
[0056] Comparative Example 2
[0057] The difference between Comparative Example 2 and Comparative Example 1 is that a 20 wt % hydrogen peroxide solution is used, the immersion time is 15 min, and the etching time is changed to 10 s.
[0058] In order to further reflect the advantages of the present invention, the present invention adopts Examples 1 to 7 and Comparative Examples 1 to 2 to passivate the CZT crystal, and the measured oxide layer thickness, CZT crystal surface uniformity, and photoresist dissolution degree are shown in Table 1. It should be noted that, through measurement, the original CZT crystal thickness is A. 1 , and the root mean square deviation of the profiles of three random thicknesses in the adjacent area is measured to be Rq 1 The thickness of the CZT crystal measured in hydrogen peroxide solution is B 1 , and the root mean square deviation of the profiles of three random thicknesses in the adjacent area is measured to be Rq 2 Finally, after etching, the root mean square deviation of the three random thickness profiles in the adjacent area is measured as Rq 3 , oxide layer thickness = B 1 -A 1 , where Rq 1 , Rq 2 , Rq 3 The smaller the value, the better the uniformity of the CZT crystal surface. It should be noted that the root mean square deviation Rq of the profile can be directly measured by the profilometer. On the other hand, the dissolution of the photoresist can be known by observation.
[0059] Table 1 CZT crystal passivation results
[0060]
[0061]
[0062] Result analysis:
[0063] 1. It can be seen from Example 1, Example 2, and Example 3 that in order to obtain a similar oxide layer thickness, the immersion time required for 30wt% hydrogen peroxide solution is long and the efficiency is low, while the oxide layer thickness generated by 50wt% hydrogen peroxide solution and 65wt% hydrogen peroxide solution in the same time is similar, and at the corresponding etching degree, the surface uniformity of the etched CZT crystal is similar, that is, under the premise of cost and efficiency, 50wt% hydrogen peroxide solution is the optimal concentration.
[0064] 2. It can be seen from Example 2, Example 4, and Example 5 that when the CZT crystal is immersed in a 50wt% hydrogen peroxide solution and etched with a 1wt% bromoglycol solution, a longer etching time is required to ensure that the oxide layer is completely etched away. When etching with a 4wt% bromoglycol solution, the surface uniformity of the CZT crystal decreases, which proves that the 4wt% bromoglycol solution will etch the CZT crystal in a short time, while the CZT crystal surface uniformity obtained with a 2wt% bromoglycol solution is better. The above conclusions prove that a bromoglycol solution with a lower concentration has a lower efficiency, but a bromoglycol solution with a higher concentration will etch the CZT crystal, and the etching time is uncontrollable. The 2wt% bromoglycol solution is the optimal concentration, and the immersion time is 10s.
[0065] 3. It can be seen from Examples 4 and 6 that when the CZT crystal is etched with a 2wt% bromine methanol solution, although the concentration is higher than that of a 1wt% bromine glycol solution, the etching time is greater than that of a 1wt% bromine glycol solution, so the efficiency is lower, and the 2wt% bromine methanol solution will also dissolve the photoresist, resulting in a poor passivation effect. Therefore, it can be seen that the best choice of etching solution is a bromine glycol solution.
[0066] 4. It can be seen from Examples 5 and 7 that when the bromoethylene glycol solution is 10wt%, the photoresist will be dissolved, thereby etching away the oxide layer under the photoresist, and the CZT crystal will also be etched, resulting in the thickness of the oxide layer being affected, thereby affecting the leakage current. It can be seen that in order to ensure that the bromoethylene glycol solution does not etch the oxide layer and CZT crystal under the photoresist, the concentration of the bromoethylene glycol solution is selected in the range of 1 to 4wt%, and the immersion time is optimally 4 to 28s.
[0067] 5. It can be seen from Example 3 and Comparative Example 1 that when the CZT crystal is immersed in a 70wt% hydrogen peroxide solution, the thickness of the oxide layer formed within the same immersion time is thicker, and then at the same etching solution concentration and etching time, the surface uniformity of the CZT crystal is affected. It can be seen that when the CZT crystal is immersed in a hydrogen peroxide solution exceeding 65wt% and the etching degree is the same, the surface uniformity of the CZT crystal decreases instead.
[0068] 6. From Example 1 and Comparative Example 2, it can be seen that when the CZT crystal is immersed in a 20wt% hydrogen peroxide solution, although the immersion time is extended, the thickness of the oxide layer is similar to that of the 30wt% hydrogen peroxide solution immersed for 10 minutes. It can be seen that when the concentration is lower than 30wt%, extending the immersion time will not affect the thickness of the oxide layer.
[0069] In summary, we found that when CZT crystals are immersed in hydrogen peroxide solution below 30wt%, the thickness of the oxide layer will not increase if the immersion time is extended. However, when immersed in hydrogen peroxide solution above 65wt%, the surface uniformity of CZT crystals is affected under the same etching effect. When immersed in hydrogen peroxide solution of 50wt%, the same effect can be achieved while maintaining efficiency, and the cost is also optimal. On the other hand, we also found that the best choice of etching solution is ethylene glycol bromide solution. Furthermore, when the concentration of ethylene glycol bromide solution exceeds 4wt%, ethylene glycol bromide solution Alcohol solution will dissolve the photoresist, resulting in a significant reduction in the passivation effect; when the concentration of bromoethylene glycol solution is between 1 and 4wt%, the higher the concentration of bromoethylene glycol solution, the more uncontrollable the etching time is, and the CZT crystal will be etched, affecting the surface uniformity of the CZT crystal; when the concentration of bromoethylene glycol solution is lower, the etching time is longer and the efficiency is lower, while when etching under 2wt% bromoethylene glycol solution, the etching time is more conducive to control, the etching time is shorter, the efficiency is higher, and it is more conducive to etching the oxide layer outside the photoresist without dissolving the photoresist, and the CZT crystal will not be etched.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A pixel-type CZT detector passivation process, It is characterized in that The steps include: Step 1: Soaking the CZT crystal in a hydrogen peroxide solution having a mass fraction of 30 to 65% of hydrogen peroxide for 1 to 10 minutes to obtain a CZT crystal having an oxide layer; Step 2: Photolithography the CZT crystal processed in step 1, covering the photolithography area with a layer of photoresist, and then immersing the CZT crystal containing the photoresist in an etching solution to etch the oxide layer outside the photoresist; Step 3: The CZT crystal processed in step 2 is cleaned, electrode-plated, and photoresist stripped in sequence to obtain a CZT crystal with an electrode connected to an oxide layer.
2. A pixel-type CZT detector passivation process according to claim 1, It is characterized in that The etching solution in step 2 is a bromoethylene glycol solution, the mass fraction of bromoethylene glycol in the bromoethylene glycol solution is 1-4%, and the immersion time is 4-28s.
3. A pixel-type CZT detector passivation process according to claim 2, It is characterized in that The mass fraction of bromoethylene glycol in the bromoethylene glycol solution is 2%, and the immersion time is 10 seconds.
4. A pixel-type CZT detector passivation process according to claim 3, It is characterized in that The mass fraction of hydrogen peroxide in the hydrogen peroxide solution in step 1 is 50%, and the soaking time is 4 minutes.
5. A pixel-type CZT detector passivation process according to claim 1, It is characterized in that The photolithography in step 2 is negative photolithography, and the photoresist formed by the negative photolithography is located above the oxide layer.
6. A pixel-type CZT detector passivation process according to claim 1, It is characterized in that The step 3 is specifically as follows: washing away the bromoethylene glycol solution remaining on the CZT crystal with water, plating an electrode on the CZT crystal, and finally stripping off the photoresist to obtain a CZT crystal with the electrode connected to the oxide layer.
7. A pixel-type CZT detector passivation process according to claim 6, It is characterized in that The stripping of the photoresist is carried out by immersing the CZT crystal after the electrode is plated in a stripping solution until the photoresist falls off and then taking it out to obtain a CZT crystal with the electrode and the oxide layer connected.
8. A pixel-type CZT detector passivation process according to claim 1, It is characterized in that The step 1 specifically comprises: before the CZT crystal is immersed in the hydrogen peroxide solution, the CZT crystal is immersed in a bromomethanol solution, wherein the mass fraction of bromomethanol in the bromomethanol solution is 1-5%, and the immersion time is 30-280s, and the CZT crystal is immersed in the hydrogen peroxide solution immediately after being immersed in the bromomethanol solution.
9. A pixel-type CZT detector, It is characterized in that It is manufactured according to the pixel-type CZT detector passivation process described in any one of claims 1 to 8.
